Justice as the Fundamental Principle in the Fulfillment of Human Rights - Khairuddin Khairuddin (Yayasan Abdurrauf Cendekia Nusantara, 2025)
Justice constitutes a fundamental principle in the fulfillment of Human Rights, functioning not merely as a moral value but also as a normative foundation within legal systems. This article aims to examine the role of justice as a core principle in the realization of human rights and its implications for state responsibility in ensuring the protection and fulfillment of fundamental rights. This study employs a normative-conceptual approach by analyzing theories of justice, international human rights instruments, and national legal frameworks. The findings indicate that procedural fulfillment of human rights without substantive justice may result in inequality and discrimination. Substantive justice is therefore essential to ensure that human rights are not only formally recognized but also effectively implemented in an equitable manner. The article concludes that the integration of justice into human rights fulfillment is a crucial prerequisite for establishing a rule of law that upholds human dignity.